Plowshares & pruning hooks: rethinking the language of biblical prophecy and apocalyptic - Sandy, D. Brent, 1947-- (Downers Grove, Illinois Intervarsity Press, 2002)
D. Brent Sandy carefully considers the language and imagery of prophecy and apocalyptic, how it is used, how it is fulfilled within Scripture, and how we should read it against the horizon of our future.
1: What Makes Prophecy Powerful?; 2: What Makes Prophecy Problematic?; 3: How Does the Language of Prophecy Work?; 4: How Does the Language of Destruction and Blessing Work?; 5: How Does the Language of Apocalyptic Work?; 6: How Have Prophecies Been Fulfilled?; 7: How Will Prophecies Be Fulffilled?
Includes bibliographical references and indexes
Keywords: Bible -- Prophecies; Bible -- Language, style; Apocalyptic literature -- History and criticism